Effects of prior cognitive exertion on physical performance: A systematic review and meta-analysis - Brown, D. M. Y.; Graham, J. D.; Innes, K. I.; Harris, S.; Flemington, A.; Bray, S. R. (Sports Medicine, 2020)
Background: An emerging body of the literature in the past two decades has generally shown that prior cognitive exertion is associated with a subsequent decline in physical performance. Two parallel, but overlapping, bodies of literature (i.e., ego depletion, mental fatigue) have examined this question. However, research to date has not merged these separate lines of inquiry to assess the overall magnitude of this effect. Objective: The present work reports the results of a comprehensive systematic review and meta-analysis examining carryover effects of cognitive exertion on physical performance. Methods: A systematic search of MEDLINE, PsycINFO, and SPORTDiscus was conducted. Only randomized controlled trials involving healthy humans, a central executive task requiring cognitive exertion, an easier cognitive comparison task, and a physical performance task were included. Results: A total of 73 studies provided 91 comparisons with 2581 participants. Random effects meta-analysis showed a significant small-to-medium negative effect of prior cognitive exertion on physical performance (g = - 0.38 [95% CI - 0.46, - 0.31]). Subgroup analyses showed that cognitive tasks lasting < 30-min (g = - 0.45) and = 30-min (g = - 0.30) have similar significant negative effects on subsequent physical performance. Prior cognitive exertion significantly impairs isometric resistance (g = - 0.57), motor (g = - 0.57), dynamic resistance (g = - 0.51), and aerobic performance (g = - 0.26), but the effects on maximal anaerobic performance are trivial and non-significant (g = 0.10). Studies employing between-subject designs showed a medium negative effect (g = -?0.65), whereas within-subject designs had a small negative effect (g = -?0.28). Conclusion: Findings demonstrate that cognitive exertion has a negative effect on subsequent physical performance that is not due to chance and suggest that previous meta-analysis results may have underestimated the overall effect.